Catalytic hydrodeoxygenation of rubber seed oil over sonochemically synthesized Ni-Mo/Î³-Al2O3 catalyst for green diesel production - Ameen, M. (2019)
Hydrodeoxygenation is one of the promising technologies for the transformation of triglycerides into long-chain hydrocarbon fuel commonly known as green diesel. The hydrodeoxygenation (HDO) of rubber seed oil into diesel range (C15âC18) hydrocarbon over non-sulphided bimetallic (Ni-Mo/Î³-Al2O3 solid catalysts were studied. The catalysts were synthesized via wet impregnation method as well as sonochemical method. The synthesized catalysts were subjected to characterization methods including FESEM coupled with EDX, XRD, BET, TEM, XPS, NH3-TPD, CO-chemisorption and H2-TPR in order to investigate the effects of ultrasound irradiations on physicochemical properties of the catalyst. All the catalysts were tested for HDO reaction at 350 Â°C, 35 bar, H2/oil 1000 N (cm3/cm3) and WHSV = 1 hâ1 in fixed bed tubular reactor. The catalyst prepared via sonochemical method showed comparatively higher specific surface area, particles in nano-size and uniform distribution of particle on the external surface of the support, higher crystallinity and lower reduction temperature as well as higher concentration of Mo4+ deoxygenating metal species. These physicochemical properties improved the catalytic activity compared to conventionally synthesized catalyst for HDO of rubber seed oil. The catalytic performance of sonochemically synthesized Ni-Mo/Î³-Al2O3 catalyst (80.87) was higher than the catalyst prepared via wet impregnation method (63.3). The sonochemically synthesized Ni-Mo/Î³-Al2O3 catalyst is found to be active, produces 80.87 wt of diesel range hydrocarbons, and it gives high selectivity for Pentadecane (18.7 wt), Hexadecane (16.65 wt), Heptadecane (24.45 wt) and Octadecane (21.0 wt). The product distribution revealed that the deoxygenation reaction pathway was preferred. Higher conversion and higher HDO yield in this study are associated mainly with the change in concentration ratio between oxidation states of molybdenum (Mo4+, Mo5+, and Mo6+) on the external surface of the catalyst due to ultrasound irradiation during the synthesis process. Consequently, the application of sonochemically synthesized non-sulphided catalysts favored mainly hydrodeoxygenation of diesel range hydrocarbon. Â© 2018 Elsevier B.V.